Validation of dynamic treatment‐couch tracking for prostate SBRT. Issue 6 (25th April 2017) - Ehrbar, Stefanie; Schmid, Simon; Jöhl, Alexander; Klöck, Stephan; Guckenberger, Matthias; Riesterer, Oliver; Tanadini‐Lang, Stephanie
Abstract : Purpose: In stereotactic body radiation therapy (SBRT) of prostatic cancer, a high dose per fraction is applied to the target with steep dose gradients. Intrafractional prostate motion can occur unpredictably during the treatment and lead to target miss. This work investigated the dosimetric benefit of motion compensation with dynamic treatment‐couch tracking for prostate SBRT treatments in the presence of prostatic motion. Methods: Ten SBRT treatment plans for prostate cancer patients with integrated boosts to their index lesion were prepared. The treatment plans were applied with a TrueBeam linear accelerator to a phantom in (a) static reference position, (b) moved with five prostate motion trajectories without any motion compensation, and (c) with real‐time compensation using transponder‐guided couch tracking. The geometrical position of the electromagnetic transponder was evaluated in the tracked and untracked situation. The dosimetric performance of couch tracking was evaluated, using Gamma agreement indices (GAI) and other dose parameters. These were evaluated within the phantoms biplanar diode array, as well as target‐ and organ‐specific. Results: The root‐mean‐square error of the motion traces (range: 0.8–4.4 mm) was drastically reduced with couch tracking (0.2–0.4 mm). Residual motion was mainly observed at abrupt direction changes with steep motion gradients. The phantom measurements showed significantly better GAI1%/1mm with tracked (range: 83.4%–100.0%) than with untracked motion (28.9%–99.7%). Also GAI2%/2mm was significantly superior for the tracked (98.4%–100.0%) than the untracked motion (52.3%–100.0%). The organ‐specific evaluation showed significantly better target coverage with tracking. The dose to the rectum and bladder showed a dependency on the anterior–posterior motion direction. Conclusions: Couch tracking clearly improved the dosimetric accuracy of prostate SBRT treatments. The treatment couch was able to compensate the prostatic motion with only some minor residual motion. Therefore, couch tracking combined with electromagnetic position monitoring for prostate SBRT is feasible and improves the accuracy in treatment delivery when prostate motion is present.